Alteration of lymphocyte subsets during a competitive swim training session - Neisler, H. M.; Bean, M. H.; Thompson, W. R.; Hall, M. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
Lymphocyte subsets across an entire training season were studied in 17 male collegiate competitive swimmers. Pre- (PRE) and post-workout (PS) samples were collected on seven occasions during the season. Neither height, weight, % body fat, haematocrit nor haemoglobin changed significantly across the PRE samples. Significant changes across time occurred in all PRE leukocyte, absolute lymphocyte, Tcell, B-cell, T-4, T-8, T4+2H4+, T4+4B4+ and NKH1 counts. Moreover, the pattern of these PRE to PS samples changed significantly after initial adaptation, during the period of greatest training stress, and again during taper. Increases in self-reported physical and psychological stress paralleled decreases in T4+4B4+ and NKHl cells and a plateau in performance.